Slip Rate of the Danghe Nan Shan Thrust Fault from 10Be Exposure Dating of Folded River Terraces: Implications for the Strain Distribution in Northern Tibet. Issue 4 (23rd March 2021) - Xu, Q.; Hetzel, R.; Hampel, A.; Wolff, R.
Abstract: The northeastward motion of the Tibetan Plateau along the Altyn Tagh strike‐slip fault causes thrust faulting in three parallel mountain ranges (Qilian Shan, Daxue Shan, and Danghe Nan Shan) in the plateau interior, and leads to NNE‐directed crustal shortening and plateau growth. While slip rates at the plateau margin (i.e., along the Qilian Shan and the Altyn Tagh fault) are well constrained, rates of thrust faulting and the strain distribution in the plateau interior remain poorly resolved. Here, we use field investigations, a high‐resolution DEM, and 10 Be exposure dating to quantify the shortening rate across the Danghe Nan Shan thrust fault from fluvial terraces, which are deformed by a growing NNE‐vergent anticline. 10 Be exposure ages from two terrace levels range from 70 ± 5 to 92 ± 7 ka. When combined with uplift values of 37–68 m along the fold hinge, the 10 Be ages yield a mean uplift rate of 0.6 ± 0.2 mm/year. Using the cross‐sectional area of the fold and the subsurface geometry of the listric thrust fault, we obtain a shortening rate of 0.8 ± 0.2 mm/year, which is consistent with the rate of elastic strain accumulation recorded by GPS data. Together with published fault slip rates and GPS data, our results indicate that northern Tibet experiences NNE‐directed shortening at a rate of ∼5 mm/year between the Qaidam Basin and the Hexi Corridor. In the plateau interior, this shortening is accommodated by several range‐bounding thrust faults and closely coupled with the eastward decrease in the slip rate of the Altyn Tagh fault. Key Points: 10 Be exposure ages for folded fluvial terraces yield a vertical slip rate of 0.6 ± 0.2 mm/year for the Danghe Nan Shan thrust fault The fault geometry derived from the folded terraces combined with fold‐area balancing yields a shortening rate of 0.8 ± 0.2 mm/year GPS data and fault slip rates suggest ∼5 mm/year of NNE–SSW‐directed shortening by thrust faulting in the interior of northern Tibet